Classification of Neighborhood Unit Cadres’ Satisfaction Levels with the Carik App Using the Naïve Bayes Method in Semper Barat Subdistrict - Frencis Matheos Sarimole; Sugiyono Sugiyono; Aditya Zakaria Hidayat; Wida Lestari (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2026)
This study aims to classify the level of satisfaction of Dasawisma cadres with the Carik application in West Semper Village by utilizing the Naive Bayes method. Data was obtained through questionnaires, which were compiled based on three main aspects: ease of use, speed of access, and the usefulness of applications in supporting cadre tasks. After the data is collected, a pre-processing and labeling process is carried out, where the level of satisfaction of respondents is categorized into two classes, namely